IMPLEMENTATION OF MADRASAH/SCHOOL SELF-EVALUATION (EDM/S) AND THEIR PROBLEMS - Fitriyah Fitriyah (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2022)
This study aims to identify potential problems and alternative solutions in implementing Madrasah/School Self-Evaluation (EDM/S). This study uses secondary data in the form of documentation of legislation, research results, evaluation reports, and other publications, and is analyzed by meta-analysis. Secondary data is sourced from guidelines for implementing EDM/S in several madrasas/schools, the media, official documents of laws and regulations, and reports on the results of related studies. The results showed that the constraints faced included aspects of concepts, instruments, infrastructure, human resources, and administration. These problems arise as a result of the lack of proper socialization, the absence of a madrasa/school commitment, and the absence of cooperation between various stakeholders, and the ability of human resources in IT skills. The alternative to overcome these problems is by making special policies at the district/city level that can be used as a legal umbrella in the planning, budgeting, and monitoring processes.